Feasibility, acceptability, and short-term impact of a brief sexually transmitted infection intervention targeting U.S. Military personnel and family members - Anjali Kunz; Amber Moodley; Donn J. Colby; Michele Soltis; Wesley Robb-McGrath; Alexandra Fairchok; Paul Faestel; Amanda Jungels; Alexis A. Bender; Edwin Kamau; Gina Wingood; Ralph DiClemente; et al. (BMC, 2022)
Abstract Background Over the past 10 years, incidence of sexually transmitted infections (STIs) has increased to record numbers in the United States, with the most significant increases observed among adolescents and young adults. The US military, where the majority of active duty personnel are 18-30 years old, has seen similar increases. However, the US military does not yet have a standardized, service-wide program for STI education and prevention. Methods The KISS intervention (Knocking out Infections through Safer-sex and Screening) was adapted from an evidence-based intervention endorsed by the US Centers for Disease Control and Prevention and consisted of a one-time, small group session. Content included STI/HIV knowledge and prevention, condom use skills, and interpersonal communication techniques. The intervention was pilot tested for feasibility and acceptability among a population of service members and medical beneficiaries at Joint Base Lewis-McChord in Washington state. Results A total of 79 participants aged 18-30 years were consented to participate in the pilot study and met entry criteria, 66/79 (82.5%) attended the intervention session, and 46/66 (69.7%) returned at 3 months for the final follow-up assessment. The intervention sessions included 31 male (47.0%) and 35 female (53.0%) participants. Almost all participants felt comfortable discussing sexual issues in the group sessions, reported that they intended to practice safer sex after the intervention, and would also recommend the intervention to friends. Knowledge about STI/HIV prevention significantly increased after the intervention, and intervention effects were maintained at 3 months. About one-fifth of participants tested positive for N. gonorrhea or C. trachomatis infection at enrollment, while none had recurrent STIs at the final visit. Use of both male and female condoms increased after the intervention. Conclusions The KISS intervention was feasible to implement in the military setting and was acceptable to the active duty service members and other medical beneficiaries who participated in the pilot project. Further studies are needed to determine if the KISS intervention, or others, effectively decrease STI incidence in active duty personnel and would be appropriate for more widespread implementation. Trial Registration Retrospectively registered as the pilot phase of clinicaltrials.gov NCT04547413 , "Prospective Cohort Trial to Assess Acceptability and Efficacy of an Adapted STI/HIV Intervention Behavioral Intervention Program in a Population of US Army Personnel and Their Medical Beneficiaries-Execution Phase."